دراسة اقتصادية تحليلية لواقع الاستثمار في زراعة الحمضيات في سورية خلال الفترة 2007-2011 (Latakia University Journal -Biological Sciences Series, 2014)
يهدف البحث إلى دراسة واقع الاستثمار في زراعة الحمضيات في سورية خلال الفترة /2007-2011/. وبينت الدراسة أن سوق الحمضيات في سورية يحتاج إلى تنظيم، وإلى ضرورة وجود جهة مستقلة(اتحاد مزارعي الحمضيات على سبيل المثال) تكون مسؤولة، بالتعاون مع الجهات المختصة، بالإشراف على إنتاج وتسويق الحمضيات، كما أوضحت الدراسة أن سوق الحمضيات في سورية تنطبق عليه مواصفات سوق المنافسة الكاملة، وأن هناك تذبذباً في قيم مرونة العرض والطلب، مما يؤشر إلى وجود عوامل أخرى غير السعر تؤثر على الطلب والعرض. وبينت الدراسة أيضاً وجود فجوة تسويقية كانت إشارتها سالبة، مما سبب في إغراق السوق بالحمضيات، إذ بلغت عام 2007 (-247.49) ألف طن، كما أن الاستثمار في الحمضيات حقق قيمة مضافة موجبة ساهمت في دعم الناتج المحلي في سورية حيث بلغت نحو 25 مليار ل.س في عام 2011. وساهم قطاع الحمضيات أيضاً في تحقيق التوازن لميزان المدفوعات، إذ بلغ صافي التدفقات النقدية الناتجة من الحمضيات في عام 2011  نحو 140 مليون دولار.The research aims at investigating  the reality of investment of the cultivation of citrus in Syria during 2007-2011. The study showed that the citrus market in Syria needs to be organized, and that there is a necessity for having an independent organization such as (Citrus Growers Union) to be responsible, in cooperation with the relevant authorities, for monitoring the production and marketing of citrus. The study also showed that the specifications of full market competition apply to the citrus market in Syria, and that there is a fluctuation in the value of flexibility of supply and demand which indicates the presence of factors other than the price which affect the supply and demand. The study also showed a marketing gap which was negative, this led to flooding the market with citrus reaching (-247.4 thousand tons) in 2007. The investment in citrus achieved a positive added-value which helped support the gross domestic product (GDP) in Syria, reaching (25 billion Syrian pounds) in 2011.The citrus sector also contributed in creating a balance of payments; outflows of citrus reaching $140 million.